Diseño de un centro de tratamiento para los vertidos de la lubrilavadora Reina de las Lajas ubicada en el barrio Centro del cantón Saquisilí - Toapanta del Valle, Sabina Del Rocio (2015)
The present work of investigation being named: DESIGN OF A CENTER FOR THE TREATMENT OF WASTE FOR THE CAR WASH NAMED “REINA DE LA LAJAS” LOCATED IN THE CENTER OF NEIGBORHOOD OF SAQUISILI, making specific reference to the determination of the levels of contamination and quality of water being utilized before, during and after the process. The study conducted determined by environmental lavatory analysis the contamination of the water utilized in the process of washing vehicles, the waste water treatment utilized with the final purpose of reusing or disposing of used waters which are compliant with the norms and within parameters of current environmental laws of Ecuador. A treatment plant was implemented with the objective of proving the data of this study with different parameters of the contaminants of the water being produced. In addition the different phases of the treatment process were outlined for the treatment of the contaminated water….